Eriocaulaceae from Serra da Canastra, Minas Gerais, Brazil - Freitas, Mariane da Silva; Trovó, Marcelo; Echternacht, Livia (Rodriguésia, 2024)
Abstract Eriocaulaceae exhibit wide diversity within the Campo Rupestre, with the Serra do Espinhaço as their richest region. However, other mountain ranges featuring Campo Rupestre, like Serra da Canastra, also harbor a significant number of species. The present work consists of the taxonomic treatment of Eriocaulaceae occurring in the Serra da Canastra, as well as an analysis of the species distribution in three main surrounding Campo Rupestre areas: the Espinhaço and Mantiqueira Ranges, and the Chapada dos Veadeiros and neighbor mountains. Thirty-one species were recorded: 19 of Paepalanthus, six of Syngonanthus, four of Comanthera, one of Eriocaulon, and one of Leiothrix. Canastra shares eight species with Espinhaço, Mantiqueira, and Veadeiros; seven with Espinhaço and Mantiqueira; two with Espinhaço and Veadeiros; five exclusively with the Espinhaço and two exclusively with Veadeiros. Seven species are endemic to Canastra: Paepalanthus claussenianus, P. canastrensis, P. polycladus, P. sericiscapus, P. sinuosus, P. uai, and Syngonanthus culcitosus. Photographs, descriptions, identification key and comments on the morphological variations and geographic distribution for each species are presented, in addition to maps of the occurrence and distribution of species in different locations. Resumo Eriocaulaceae são amplamente diversificadas nos Campos Rupestres, sendo que a Serra do Espinhaço é a região mais rica em espécies. Entretanto, outras áreas também abrigam um número expressivo de espécies, como a Serra da Canastra. O presente trabalho consiste na flora de Eriocaulaceae na Serra da Canastra, bem como na análise de distribuição das espécies compartilhadas com as três maiores áreas de Campo Rupestre vizinhas: a Cadeia do Espinhaço, a Serra da Mantiqueira e a Chapada dos Veadeiros e montanhas vizinhas. Foram registradas 31 espécies, sendo 19 de Paepalanthus, seis de Syngonanthus, quatro de Comanthera, uma para Eriocaulon e uma para Leiothrix. A Canastra compartilha oito espécies com o Espinhaço, Mantiqueira e Veadeiros; sete com Espinhaço e Mantiqueira; duas com Espinhaço e Veadeiros; cinco exclusivamente com o Espinhaço e duas exclusivamente com Veadeiros. Sete espécies são endêmicas da Canastra: Paepalanthus claussenianus, P. canastrensis, P. polycladus, P. sericiscapus, P. sinuosus, P. uai e Syngonanthus culcitosus. São apresentadas fotografias, descrições, chave de identificação e comentários sobre as variações morfológicas e distribuição geográfica para cada uma delas, além de mapas de ocorrência e distribuição das espécies nas diferentes localidades.